Farmers' practices and community management of irrigation: why do they not match in Fatnassa oasis? - Ghazouani, Wafa; Marlet, S.; Mekki, I.; Harrington, Larry W.; Vidal, Alain (Wiley, 2012)
Community-managed irrigation systems are commonly faced with problems of low system-level performance. A comprehensive survey was undertaken to assess and quantify the causes of the low irrigation performance in a community-managed oasis in southern Tunisia. At the irrigation system level, results showed that irrigation intervals were double those that had been expected (19-21 days). The main cause was inappropriate farmers' practices at eld level where the irrigation duration was almost twice the expected 10 h ha-1. The extension of date palm plantation and technical dysfunctions played a less important role as they were counterbalanced by cancellation of irrigation in some plots. At the eld scale, excessively long irrigation duration resulted from the joint effects of small elds, poor maintenance of eld-level water delivery systems, uncontrolled night irrigation events and low farmer commitment. This situation emphasizes the question of ef ciency and sustainability of irrigation systems when farmers subvert collective rules. Further, the situation raises the question of equity among farmers which hinders their support for the water users' association and the strict application of water allocation rules. These ndings should help identify an appropriate approach and lead to positive changes in the management of community irrigation systems.